Monitoring Composites under Bending Tests with Infrared Thermography. (7th November 2012) - Meola, Carosena; Carlomagno, Giovanni Maria; Bonavolontà, Carmela; Valentino, Massimo
Abstract : The attention of the present paper is focused on the use of an infrared imaging device to monitor the thermal response of composite materials under cyclic bending. Three types of composites are considered including an epoxy matrix reinforced with either carbon fibres (CFRP) or glass fibres (GFRP) and a hybrid composite involving glass fibres and aluminium layers (FRML). The specimen surface, under bending, displays temperature variations pursuing the load variations with cooling down under tension and warming up under compression; such temperature variations are in agreement with the bending moment. It has been observed that the amplitude of temperature variations over the specimen surface depends on the material characteristics. In particular, the presence of a defect inside the material affects the temperature distribution with deviation from the usual bending moment trend.